Beyond interpretivism? New encounters with technology and organization : IFIP WG 8.2 Working Conference on Information Systems and Organizations, IS & O 2016, Dublin, Ireland, December 9-10, 2016, Proceedings /: IFIP WG 8.2 Working Conference on Information Systems and Organizations, IS & O 2016, Dublin, Ireland, December 9-10, 2016, Proceedings. (2016) - Unknown
No abstract available